The synergistic interaction of vitamin D deficiency and insomnia on dizziness-related handicap in patients with benign paroxysmal positional vertigo - Tang, Bo; Luo, Minghua; Wang, Dan; He, Yuqin; Zhang, Chuang; Yu, Xiaojun (Frontiers in Neurology, 2025)
BackgroundWhile insomnia and vitamin D deficiency are known risk factors for BPPV, their interactive effect on the dizziness-related handicap is unknown. Given that both may independently promote pro-inflammatory states, a synergistic interaction is biologically plausible. Therefore, this study aimed to investigate both the independent and interactive effects of insomnia and 25-OH-D levels on the dizziness-related handicap in BPPV patients. We specifically hypothesized that insomnia amplifies the detrimental impact of low vitamin D, aiming to provide an empirical basis for integrated clinical management strategies.MethodsIn this cross-sectional study, 125 patients with BPPV were enrolled. Serum 25-OH-D levels and Dizziness Handicap Inventory (DHI) scores were measured. A multivariable linear regression model, refined by a systematic variable selection procedure, was used to assess the effects of insomnia and 25-OH-D on log-transformed DHI scores after adjusting for potential confounders.ResultsAfter multivariable adjustment in the final parsimonious model, insomnia, lower 25-OH-D levels, and their interaction term all remained highly significant predictors of higher dizziness-related handicap (all p < 0.01). The interaction indicated that the negative association between 25-OH-D and DHI was significantly stronger in patients with insomnia.ConclusionInsomnia and vitamin D deficiency are independently associated with greater dizziness-related handicap in BPPV patients, and they demonstrate a significant synergistic interaction. However, due to the study’s design, a definitive causal relationship cannot be established. Assessing and managing both conditions may be crucial for mitigating the handicap imposed by BPPV.